GE_GERICHTE P/7884/2023 vom 28. September 2023 - GE Cour de justice (2023)
ADMINISTRATION DES PREUVES;CONDITION DE RECEVABILITÉ;INVESTIGATION SECRÈTE;AGENT PROVOCATEUR | CPP.141; CPP.285a; CPP.298; CPP.286